Penerapan Perda No. 8 Tahun 2015 Terkait Pengalihan Fungsi Trotoar untuk Berjualan PT.Telkomsel di Bangkalan - Durratun Afifah; Sholeh Hoddin; Sumriyah Sumriyah (Birokrasi: JURNAL ILMU HUKUM DAN TATA NEGARA, 2024)
Road Users are those who have the right to use and get guaranteed order on the road. In addition, road users are also specified with pedestrians and motorcycle users. In this case, the use of public facilities or road sidewalks that become places for pedestrians, as regulated in Article 19 C of Regional Regulation Number 8 of 2015 concerning the Implementation of Roads and Transportation. In the Bangkalan area there are many violations, one of which is PT. Telkomsel, however, how about the procedures regarding marinating that can be done to use sidewalks has not been further regulated, and the application of sanctions for those who violate the provisions of the law is not clearly regulated.